Stercoral Colitis: Advanced Nursing and Technical Competencies in Acute Injury Management - Al Name, Abdullah Ibrahim Hassan; Sattam Saleh Mohammd Alshakrah; Atheer Hamoud Alotaibi; Reem Ayedh Alahmari; Hadeel Abdullah Almusaad; Laila Ahmed Mohammed Oraibi; Fatimah Ahmad Mohammad Oraibi; Aminah Khalaf Noman Alshamari; Ali Abdullah Mohammed Aldosari; Mubarak Mohammad Al Dosary (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Stercoral colitis is a serious inflammatory and ischemic condition of the colon caused by severe, chronic fecal impaction. Hardened fecal masses (fecalomas) exert persistent pressure on the colonic wall, leading to mucosal ulceration, ischemia, and risk of catastrophic perforation. It predominantly affects high-risk populations, including the elderly, immobile, and those with neurologic or psychiatric conditions. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review aims to outline the pathophysiology, clinical presentation, diagnostic approach, and evidence-based management of stercoral colitis, with a focus on the acute nursing and technical competencies required for effective intervention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A comprehensive synthesis of current literature is presented, detailing the etiology, epidemiology, and diagnostic pathway. Emphasis is placed on the critical role of contrast-enhanced computed tomography (CT) for diagnosis and risk stratification. Management strategies, from conservative disimpaction to emergent surgical resection, are discussed. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diagnosis hinges on clinical suspicion in at-risk patients and is confirmed by CT findings of fecal impaction, colonic dilation (>6 cm), wall thickening (>3 mm), pericolonic fat stranding, and mucosal discontinuity indicating ischemia. Initial management for stable patients involves bowel decompression via manual or endoscopic disimpaction, bowel rest, and antibiotics. Signs of peritonitis, perforation, or failed conservative therapy mandate emergent surgical resection, typically with colostomy formation. Mortality is high (32-60%), especially with perforation or extensive (>40 cm) colonic involvement. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Stercoral colitis is a preventable, life-threatening complication of chronic constipation. Outcomes depend on early recognition, prompt CT imaging, and timely intervention. Successful management requires an interprofessional team approach, integrating acute surgical care with long-term strategies to prevent recurrence.